An overview of environmental disaster in Malaysia and preparedness strategies - Abdul Rahman, Haliza (Tehran University of Medical Sciences, 2014)
Malaysia is affected by moderate environmental disasters but seldom affected by severe disaster. Cameron Highland mud floods 2013, Hulu Langat landslide 2011, tsunami 2004 and Highland Tower 1993 are some of environmental disaster in Malaysia. Some of these disasters carry heavy price tags as property and lives are damaged beyond full compensation and repair and health effects as well. This paper was focused on environmental disaster in Malaysia with reference to flood and landslide. The scope of this paper is to provide input for a clearer understanding of these disasters and how public could be safe from these hazards with preparedness strategies. This paper involved with secondary data collected from journal, proceedings, books, related agencies and internet sources as well. Normally, humankind is capable of saving their self and Earth as well, if they recover the principles of solidarity, complementarity and harmony with nature in contraposition to the reign of competition, profits and rampant consumption of natural resources. They also must strongly support a sustainable development and a sustainable land use concept in order to sustain the environment from degrades. In addition, community-based disaster preparedness is essential in preventing and responding to the full array of environmental disasters in keeping human losses as low as possible. Ways must be found to ensure that a community is strengthened, becoming less fragile and less susceptible to environmental disaster impact. In addition, community needs to be assist in order to survive despite receiving the impact of severe disasters.